Decisional Needs of the Parents with Regard to aTD Rubella Containing Vaccines in Kalutara District, Sri Lanka - Liyanage, P.; Goonewardena, C.S.E.; Palihawadena, P. (Sri Lanka Medical Association, 2015)
Introduction and objectives: Decisional needs of the people with regard to vaccination cannot be assessed by the level of coverage of the vaccine. Method: Decisional needs and information needs of the parents was carried out using an interviewer administered questionnaire developed according to the Ottawa Decision Support Framework, Focus Group Discussions and Decision Conflict Scale. Results: The response rate for these questions was 800 (100%) and total of 416 (52%) mothers, 320 (40%) fathers and 64(8%) guardians were interviewed. Parents/ guardians perceive many benefits of the vaccination. The parents/guardians seek information about the pathogenesis of the diseases, immunization programme, and safety of the vaccines and the competency of the public health staff to handle the emergencies. Most parents take decisions collectively and parents trust public health staff as reliable sources of information and prefer leaflets as educational tools. During any crisis such as adverse event these parents/guardians would seek information and usually develop decisional conflict due to lack of reliable information. There was a negative correlation between score of the knowledge on rubella and rubella containing vaccines and the score of the decisional conflict regard to rubella containing vaccines and it was significant (P <0.01). Conclusion: Parents can develop decisional conflict during crisis due to lack of reliable information.
Keywords: vaccination; parents; decisional conflict